'Hopa!': exploring Balkanology in South African popular culture - Mhlongo, Zinaida (My University, 2014)
This thesis is a study of a popular music culture in South Africa called Balkanology. The research examines Balkanology as a club culture, explores its constituent elements, documents and then interprets Balkanology as a musical scene in South Africa. I examine Balkanology, its complexities and its social relevance, practices and processes. The thesis addresses four main questions: Why is Balkan music chosen in particular? In what ways does the Balkanology music scene imagine ‘the Balkan’? Who are its participants and why are they attracted to Balkanology? How is a culture defined by exploring musical and cultural references? The research is located broadly within ethnomusicology and was conducted using ethnographic research methods, including participant observation and informal interviews. In addition, the research related to my performances as a vocalist, where I explore different aspects of being Balkan and Balkan-inspired music, to see how composers have used Eastern European and Middle Eastern music, as well as how it is appropriated and integrated into western art music, and contemporary popular music. I first provide background context for post-communist Eastern European popular music, outlining a genealogy of this music and how Balkanology music is sourced, as well as the way in which it draws from these popular music genres. Descriptions of several Balkanology events and analysis of some of the music played, and the semiotics of visual and performance elements of Balkanology form the body of the thesis. The findings from the research are integrated with literature pertaining to the ways in which Balkan music has been interpreted in popular music, and appropriated or re-imagined in Balkanology specifically. In addressing the question of what Balkanology means in South Africa, particularly what it means to its participants, I use the following interpretative categories: Balkanology as “little culture” (McCracken 1997); exoticism and gypsyness; nostalgia and the vibe; and an “imagined community” (Anderson 1983). The findings are that Balkanology represents a space where Balkan musical and cultural origins are transported v and interpreted locally in a South African context. I conclude that this is a unique form of electronic dance music that uses Balkan music to create an “imagined culture” of the exoticised gypsy and their music, combined with theatrical elements and parodies of Balkan images and people.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, Music, 2013